2021
DOI: 10.3390/ijms222212112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Metabolic Mechanism of Low-Intensity Pulsed Ultrasound Improving Muscle Atrophy in Hindlimb Unloading Rats

Abstract: Low-intensity pulsed ultrasound (LIPUS) has been proved to promote the proliferation of myoblast C2C12. However, whether LIPUS can effectively prevent muscle atrophy has not been clarified, and if so, what is the possible mechanism. The aim of this study is to evaluate the effects of LIPUS on muscle atrophy in hindlimb unloading rats, and explore the mechanisms. The rats were randomly divided into four groups: normal control group (NC), hindlimb unloading group (UL), hindlimb unloading plus 30 mW/cm2 LIPUS irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Based on the KEGG enrichment results, 50 metabolic pathways were enriched between the 10%FBS and 5%FBS+APE groups, and the top 20 metabolic pathways are listed in Table . In comparison to the 10%FBS group, the upregulated aspartate aminotransferase in the 5%FBS+APE group was involved in alanine, aspartate, and glutamate metabolism, as well as the phenylalanine, tyrosine, and tryptophan biosynthesis pathways (Table S4), and these two pathways are known to be important in the proliferation of myoblasts . On the other hand, casein kinase downregulated the Wnt signaling pathway in comparison to the 10%FBS group.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the KEGG enrichment results, 50 metabolic pathways were enriched between the 10%FBS and 5%FBS+APE groups, and the top 20 metabolic pathways are listed in Table . In comparison to the 10%FBS group, the upregulated aspartate aminotransferase in the 5%FBS+APE group was involved in alanine, aspartate, and glutamate metabolism, as well as the phenylalanine, tyrosine, and tryptophan biosynthesis pathways (Table S4), and these two pathways are known to be important in the proliferation of myoblasts . On the other hand, casein kinase downregulated the Wnt signaling pathway in comparison to the 10%FBS group.…”
Section: Resultsmentioning
confidence: 97%
“…In comparison to the 10%FBS group, the upregulated aspartate aminotransferase in the 5%FBS+APE group was involved in alanine, aspartate, and glutamate metabolism, as well as the phenylalanine, tyrosine, and tryptophan biosynthesis pathways (Table S4), and these two pathways are known to be important in the proliferation of myoblasts. 43 On the other hand, casein kinase downregulated the Wnt signaling pathway in comparison to the 10%FBS group. Studies have demonstrated that the activation of the Wnt signaling pathway could promote cell proliferation and differentiation, 44 suggesting that APE supplementation might not fully replace serum and require additional bioactive substances.…”
Section: Proteomics Analysismentioning
confidence: 96%
“…The energy of LIFUS can be sent through the surface tissue and focused on the target tissue at a speci c depth, producing biological effects, and makeing tissue cell changes (11). Low-frequency and low-dose ultrasound do not produce destructive thermogenic reactions, it is more commonly used in the repairing muscle injury, promoting fracture healing, and in other elds of physiotherapy (12,13). LIFUS can promote uterine contraction and reduce the duration of postpartum lochia.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al studied the effect of LIPUS on improving muscle atrophy by applying 30 mW/cm 2 and 80 mW/cm 2 of LIPUS. Their results showed that LIPUS had a tendency to prevent muscle strength loss, but there was no significant difference [ 28 ]. We used sound intensities of 50 mW/cm 2 and 150 mW/cm 2 here to stimulate muscles.…”
Section: Discussionmentioning
confidence: 99%